Acute Radial Artery Injury Associated with Distal Radius Fracture: Case Series and Literature Review - Kastanis G; Chaniotakis C; Siligardou MR; Tsioupros A; Kapsetakis P; Pantouvaki A (Medical Science: Trends and Innovations Vol. 2, 2025)
Distal Radius fractures (DRF) are the most common injuries encountered in the emergency department, indifferent age or sex. Cases in which distal radius fractures are associated with vascular injury of the radial or ulna artery are very rare and are reported to as complications of internal or external fixation of the DRF. In the literature, only three cases have been analyzed for this complex injury (DRF and laceration of the radial artery) which presents a unique challenge in terms of diagnosis and treatment management. The aim of this study is to analyze three cases of simultaneous DRF and radial artery injuries and to compare our results with those reported in the literature, focusing on the incidence and management of these injuries. The recognition of these complex injuries should be detected or, at least, the clinical suspicion of these injuries should be increased through the emergency department physicians.